Refugee children in Europe on the eve of World War II. Issue 2 (3rd April 2019) - Stuart, Paul H.
ABSTRACT: In the summer of 1939, on the eve of World War II, Children's Bureau social workers Elsa Castendyck visited four European countries to investigate the care of refugee children. Her report was published in the Social Service Review in December, after the German invasion of Poland and the declaration of war by France and Great Britain, and is reprinted here.